Attraction versus production in restoration: spatial and habitat effects of shellfish reefs for fish in coastal seascapes. Issue 7 (20th June 2021) - Gilby, Ben L.; Olds, Andrew D.; Chapman, Susie; Goodridge Gaines, Lucy A.; Henderson, Christopher J.; Ortodossi, Nicholas L.; Didderen, Karin; Lengkeek, Wouter; van der Heide, Tjisse; Schlacher, Thomas A.
Abstract : Restored shellfish reefs provide valuable habitat for fish, but it is not clear how different approaches affect performance, and either promote the development of new fish populations (i.e. "production") or simply attract individuals from the broader seascape (i.e. "attraction"). We measured the effects of a 1.5 ha shellfish reef restoration site on fish assemblages in Pumicestone Passage in eastern Australia, which contains replicates of six different restoration units: shell patch reefs, crates of shells, and biodegradable matrix, and each had replicates with and without live oysters. Fish were surveyed before restoration and then every 6 months for 30 months with baited (at restoration and control sites) and unbaited (at 106 sites across the seascape to detect potential fish attraction, and at the different restoration units) underwater cameras. Shellfish reef restoration represents an addition to the carrying capacity of Pumicestone Passage for fish for two key reasons. First, restoration significantly enhanced the diversity and abundance of fish assemblages and the density of harvestable fish at the restoration site by 3.8, 10.7, and 16.4 times, respectively. Second, fish distributions across the broader seascape did not change in response to succession at the restoration site. Fish assemblages did not differ between restoration units or the presence or absence of oysters. These findings further support the notion that restored shellfish reefs significantly enhance fish abundance and diversity and that restored reefs can enhance the overall carrying capacity of seascapes for fish, rather than simply centralizing them at restoration sites.